Impact of COVID-19 infection on sports performance of elite university athletes - Kim, S.-H.; Park, J.-M.; Kim, Y.-H.; Kim, T.; Park, J.-C. (The Journal of Sports Medicine and Physical Fitness, 2023)
BACKGROUND: Cardiopulmonary functions of athletes can be affected by the Coronavirus disease 2019 (COVID-19). This study aimed to investigate athletes` pattern of returning to sports after COVID-19, their experience of COVID-19-associated symptoms, and the disturbance in sports performance caused by the symptoms. METHODS: Elite university athletes who were infected with COVID-19 in 2022 were recruited for the survey and the data for 226 respondents were analyzed. Information about COVID-19 infection and the degree of disturbance in ordinary training and competition was collected. Their returning pattern to sports, the prevalence of COVID-19 symptoms, the degree of disturbance in sports by related symptoms, and factors associated with disturbance in sports and fatigue were analyzed. RESULTS: Results showed that 53.5% of the analyzed athletes returned to ordinary training immediately after quarantine, while 61.5% experienced disturbance in ordinary training, and 30.9% experienced that in competition. Most prevalent COVID-19 symptoms were lack of energy, easy fatiguability and cough. Disturbance in ordinary training and competition were mainly related to generalized, cardiologic, and respiratory symptoms. Women and those with severe and generalized symptoms had significantly higher odds of experiencing disturbance in training. Those with cognitive symptoms had higher odds of being "fatigue case." CONCLUSIONS: More than half of the athletes returned immediately to sports after the legal quarantine period of COVID-19 infection and experienced disturbance in ordinary training by related symptoms. Prevalent COVID-19 symptoms and the associated factors causing disturbance in sports and fatigue case were also revealed. This study will be helpful to establish the safe return guidelines essential for athletes after COVID-19.